USM RANKS NO. 8 IN THE WORLD BY CWUR FOR MATERIALS SCIENCE, PAPER AND WOOD - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 3 April 2017 Universiti Sains Malaysia (USM) continues to soar upwards when it is ranked No. 8 in the world for Materials Science, Paper and Wood by the Center for World University Rankings (CWUR) by Subjects for 2017, released today.